Kształtowanie się ustroju kolegiów orzekających w Polsce Ludowej (1952-1956) - Łysko, Marcin (Czasopismo Prawno-Historyczne, 2018)
In December 1951, a collegiate model of adjudicating on petty offences was introduced in Poland. The adjudicating boards were established at the local organs of state administration and included a member of the public sitting in them. Those organs drew lists of candidates for members of the adjudicating boards, who were appointed by work places (factories, plants, etc.) and social organisations. The lists were mechanically approved by national councils. It was only in 1955 when candidates were appointed based on their relevant skills and background. However, in very small units of administration (gromada), members of the adjudicating boards lacked basic administrative experience and often committed gross violations of law. Consequently, at the turn of 1956, the common opinion demanded liquidation of the penal-administrative adjudication power of adjudicating boards in gromadas.